(untitled) (Sebha University Conference Proceedings, 2025)
Radiofrequency ablation is a type of hyperthermia treatment for cancer that uses high-frequency radio waves to heat and destroy cancer cells. A thin needle is inserted into biological tissue, and the radiation emitted by the antenna is absorbed by the tissue and causes the cancer cells to heat up. The temperature increase must reach a certain degree to destroy cancer cells, but it must be less than a certain value to avoid damaging normal, healthy cells. This is why hyperthermia treatment must be carefully monitored, and numerical simulations are useful and may provide valuable information. The bioheat equation and Maxwell’s equations are solved using the finite element method in the computer program and the electrical and thermal effects are analyzed to determine the temperature distribution.The damaged part of cancer cells. This study addressed the effect of both operating voltage and heating time on the performance of the antenna used in treatment. The results obtained showed that the temperature distribution and the damaged part of liver cancer are strongly affected by the equations of operating voltage and heating time.